Vietnam Mosaic of contrasts - Réhahn (Hồng Đức, 2016)
is a compilation of 145 best photos from Réhahn. This BIG COFFEE TABLE BOOK (2.3kg, 28x33cm) is a diary of the French photographerâ€™s journey in his new homeland, Vietnam, and its people, culture, lifestyle. Réhahnâ€™s sharing of what he has encountered and learned throughout his first 3 years travel in this country allow the world and most Vietnamese to discover something beyond what usually seen in Vietnam.